2013
DOI: 10.1002/jbmr.2013
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow composition, diabetes, and fracture risk: More bad news for saturated fat

Abstract: I n this month's issue, Patsch and colleagues(1) offer ample food for thought for anyone interested in marrow adipocytes, the enigmatic endosteal fat cells whose developmental origins, function, and impact on bone mass are currently subjects of active investigation.(2) Marrow fat is often associated with low bone mass, as in anorexia nervosa, aging, and osteoporosis, but is also present in normal bone in complex age-, sex-, and sitespecific patterns. (3)(4)(5) Although marrow adipocytes were historically assum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…On the whole, these data demonstrate the complexity of the relationship between exogenous lipid intake, MAT and bone health. Of note, the concept that the FA profile as well as the amount of marrow adipocytes may be relevant for skeletal preservation is emerging (59,60). Recent experimental data suggest that FA and lipotoxicity could play a role in the initiation and/or evolution of metabolic bone diseases such as osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…On the whole, these data demonstrate the complexity of the relationship between exogenous lipid intake, MAT and bone health. Of note, the concept that the FA profile as well as the amount of marrow adipocytes may be relevant for skeletal preservation is emerging (59,60). Recent experimental data suggest that FA and lipotoxicity could play a role in the initiation and/or evolution of metabolic bone diseases such as osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…The composition as well as the quantity of marrow fat may be relevant for skeletal health ( 47 ). The relative amounts of saturated and unsaturated lipids in marrow fat can be measured non-invasively with MR spectroscopy, allowing exploration of this aspect of marrow fat composition.…”
Section: Lipid Composition Of Marrow Fat Also Associated With Bone Dementioning
confidence: 99%
“…The increased fracture risk in diabetes may be due to increasing bone fragility caused by diabetes or an increased incidence of falling, which is related to diabetic complications [ 22 ]. Several studies have suggested that bone fragility in diabetes is caused by adiposity, insulin resistance, fatty acid composition, and hormones [ 23 – 24 ]. Marrow fat may negatively affect bone fragility in diabetes.…”
Section: Discussionmentioning
confidence: 99%